2018
DOI: 10.3389/fmicb.2018.01936
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nitric Oxide Production in Activated Macrophages Caused by Toxoplasma gondii Infection Occurs by Distinct Mechanisms in Different Mouse Macrophage Cell Lines

Abstract: Toxoplasma gondii, the causative agent of toxoplasmosis, is a widespread intracellular parasite able to infect virtually any nucleated cell. T. gondii infection of activated macrophages inhibits nitric oxide (NO) production; however, parasite effectors responsible for this block have not been defined. Macrophage populations are extremely heterogeneous, responding differently to stimuli and to parasite infection. Here we evaluated the inhibition of NO production caused by T. gondii infection of J774-A1 and RAW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Thus, it is possible conclude that meloxicam and celecoxib induce a pro-inflammatory immune response, which triggers significant reduction in T. gondii infection. Many studies demonstrated the important protective role of IFN-γ, nitrite (Gazzinelli et al, 1994; Lang et al, 2007; Kemp et al, 2013; Koblansky et al, 2013; Behnke et al, 2017; Abreu-Cabral et al, 2018), IL-17A (Kelly et al, 2005), MIF (Ferro et al, 2008; Flores et al, 2008; Terrazas et al, 2010; Gomes et al, 2011, 2018; Barbosa et al, 2014), TNF and IL-6 (Castro et al, 2013; Barbosa et al, 2014, 2015) during infection by T. gondii . Our recent studies showed that IL-6, TNF and MIF are the most important cytokines involved in the immune response to T. gondii in human trophoblast cells, human explants from third trimester and murine maternal-fetal interface, allowing a significant reduction in the vertical transmission of the parasite (Barbosa et al, 2015; Silva et al, 2017; Gomes et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible conclude that meloxicam and celecoxib induce a pro-inflammatory immune response, which triggers significant reduction in T. gondii infection. Many studies demonstrated the important protective role of IFN-γ, nitrite (Gazzinelli et al, 1994; Lang et al, 2007; Kemp et al, 2013; Koblansky et al, 2013; Behnke et al, 2017; Abreu-Cabral et al, 2018), IL-17A (Kelly et al, 2005), MIF (Ferro et al, 2008; Flores et al, 2008; Terrazas et al, 2010; Gomes et al, 2011, 2018; Barbosa et al, 2014), TNF and IL-6 (Castro et al, 2013; Barbosa et al, 2014, 2015) during infection by T. gondii . Our recent studies showed that IL-6, TNF and MIF are the most important cytokines involved in the immune response to T. gondii in human trophoblast cells, human explants from third trimester and murine maternal-fetal interface, allowing a significant reduction in the vertical transmission of the parasite (Barbosa et al, 2015; Silva et al, 2017; Gomes et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that T. gondii has the ability to evade the cytotoxic effect of nitric oxide by inhibiting the production of NO in mouse activated macrophages [27,28]. Cabral [29] suggest that inhibition of NO production in activated macrophages infected with T. gondii is a general phenomenon, but the suppression of iNOS varies depending on the macrophage cell line. The increase in the percentage of activated macrophages, as well as the production of intracellular nitric oxide in mice treated with immunobiotics, show that inhibition of NO production by T. gondii can be reversed after administration of viable Lc, thereby increasing the microbicidal capacity of activated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models are not strictly necessary for preclinical assessment of probiotics. While humanized animal models can be implemented (Table 1), it is highly challenging to develop ones that simulate microbe-host interaction in humans for niches demonstrating unique physiological features such as the lactobacilli-dominated vaginal niche characterized by a low pH (Miller et al, 2016). Human-based in vitro and ex vivo models followed by small studies with healthy volunteers and larger clinical intervention studies are invariably required to draw more precise and relevant conclusions on probiotic safety, action, and health benefits.…”
Section: In Vitro Models In Probiotics Researchmentioning
confidence: 99%